1976
DOI: 10.1111/j.1365-2389.1976.tb01979.x
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of Soil Organic Matter and Its Carbon Isotope Content in a Chronosequence of Soils Developed on Aeolian Sand in New Zealand

Abstract: Soil organic matter was extracted by a mixture of O * I M Na4P20,: O'IM NaOH from a chronosequence of weakly weathered soils developed on aeolian sand, and fractionated into humin (non-extractable), humic acid, and fulvic acid. The mass of total organic carbon in the profiles, the 14C content and the 13C/12C ratios were also determined.The weight of total carbon increased rapidly at first and then gradually without attaining a steady state. This trend was also shown by the humin and fulvic acid fractions, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
2

Year Published

1980
1980
2003
2003

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 11 publications
3
47
0
2
Order By: Relevance
“…Studies attempting to understand the influence of a specific factor (e.g., temperature or moisture) on soil properties have found it useful to identify a suite of soils for which the factor in question varies whereas the others are held constant (1)(2)(3)(4). This approach has been used successfully to look at the role of temperature (3,5) and time (6)(7)(8)(9)(10) on the turnover of soil C. Ecosystem models such as CENTURY (11,12), CASA (13), or the Rothamsted model (14,15) predict the sensitivity of soil C inventory and turnover to climate, vegetation, and parent material, but as yet few data exist to test these predictions. Parameterizations of decomposition used in these models are based on empirical fits to specific calibration sites and may not include enough basic understanding of the interaction between plant substrates and the soil environment to make successful predictions in different environments (16).…”
mentioning
confidence: 99%
“…Studies attempting to understand the influence of a specific factor (e.g., temperature or moisture) on soil properties have found it useful to identify a suite of soils for which the factor in question varies whereas the others are held constant (1)(2)(3)(4). This approach has been used successfully to look at the role of temperature (3,5) and time (6)(7)(8)(9)(10) on the turnover of soil C. Ecosystem models such as CENTURY (11,12), CASA (13), or the Rothamsted model (14,15) predict the sensitivity of soil C inventory and turnover to climate, vegetation, and parent material, but as yet few data exist to test these predictions. Parameterizations of decomposition used in these models are based on empirical fits to specific calibration sites and may not include enough basic understanding of the interaction between plant substrates and the soil environment to make successful predictions in different environments (16).…”
mentioning
confidence: 99%
“…A test of the efficiency of any fractionation method at isolating a relatively homogeneous (in terms of turnover) organic matter pool is a comparison of the observed 14C increase since atmospheric weapons testing (Goh, Stout and O'Brien 1984;Balesdent 1987;Trumbore, Vogel and Southon 1989;Trumbore 1993). These tests have shown that, although no fractionation method is completely successful, separation of organic matter by density, followed by hydrolysis in 6N HCI, does leave a residual collection of compounds, which, on average, turn over more slowly than the hydrolyzed portions of SOM (Campbell et al 1967;Scharpenseel, Ronzani and Pietig 1968;Mattel and Paul 1974;Goh et al 1976;Goh, Stout and Rafter 1977;Anderson and Paul 1984;Goh et al 1984;Trumbore, Vogel and Southon 1989;Trumbore, Bonani and Wolfli 1990;Scharpenseel and Becker-Heidmann 1992;Trumbore 1993;Trumbore, Chadwick and Amundson 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Often only the uppermost soil horizon is used in studying and modeling organic matter decomposition, as in the 5-box model of Jenkinson and Rayner (1977). Goh et al (1976) and Goh, Stout and Rafter (1977) distinguished between topsoil and subsoil. Scharpenseel, Schiffmann and Hintze (1984) dated each horizon or even 5cm layers in special cases.…”
Section: Introductionmentioning
confidence: 99%